Fulminant acute renal failure due to hemoglobin C/β-thalassemia in adolescents: Diagnostic challenge in the face of hypertensive nephropathy and thrombotic microangiopathy (Research, Society and Development, 2025)
Introduction:The challenge of fulminant renal failure in adolescents is addressed, where complex hematological factors such as hemoglobinopathy C with β-thalassemia converge, triggering hemolysis and severe tubular damage. Objective: The purpose of this report is to describe the clinical chronology, laboratory findings, and therapeutic management of an unusual condition: an unrecognized hemoglobin C/β-thalassemia, triggering fulminant AKI in the context of severe hypertension and suspected TMA Case Presentation: A 17-year-old adolescent presented with edema and dyspnea, exhibiting critical hypertension (200/130 mmHg) and anuria. Tests revealed metabolic acidosis, creatinine of 31.2 mg/dL, and anemia of 6.9 g/dL, without thrombocytopenia. Upon ruling out microangiopathic hemolysis due to the absence of schistocytes, electrophoresis confirmed hemoglobinopathy C (35.3%) and β-thalassemia (Hb A₂ 62.1%). Despite dialysis and ventilatory support, the patient died from multi-organ failure. Discussion: The lethal pathogenic interaction between massive heme release, oxidative stress, and pigment nephrotoxicity, aggravated by malignant hypertension, is analyzed; this mechanism mimics microangiopathic conditions, complicating diagnosis. Conclusion: The case underscores the urgency of investigating structural hemoglobinopathies in young patients with acute renal failure and unexplained anemia. Early electrophoresis is recommended in these scenarios to avoid therapeutic delays and foster interdisciplinary cooperation between nephrology and hematology.